2015
DOI: 10.1080/19475705.2015.1084953
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of flood inundation mapping from MODIS and ALOS satellites for Pakistan

Abstract: The paper presents a moderate resolution imaging spectroradiometer (MODIS) time-series imagery-based algorithm for detection and mapping of seasonal and annual changes in flood extent, and tests this using the flooding of the Indus River Basin in 2010 À one of the greatest recent disasters that affected more than 25 million people in Pakistan. The algorithm was applied to produce inundation maps for 10 annual flood seasons over the period from 2000 to 2011. The MODIS flood products were validated in comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 21 publications
(28 reference statements)
0
15
0
Order By: Relevance
“…For instance, the flood of 2008 in Kosi River was mostly attributed to a collapse of the embankment near the Kushaha village of Sunsari district at the Indo-Nepal border and as a result, it caused flooding in Purnia, Madhepura, Saharsa, Supaul, Kahagaria, Katihar and Araria districts [61,62]. In the 2010 flood event, it was reported that Khagaria, Supaul, Araria, Katihar, and Madhepura districts were most adversely affected and the detailed flood maps based on ALOS and RADASAT satellite can be found in Amarnath et al [63] and FMISC Flood Report [34].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the flood of 2008 in Kosi River was mostly attributed to a collapse of the embankment near the Kushaha village of Sunsari district at the Indo-Nepal border and as a result, it caused flooding in Purnia, Madhepura, Saharsa, Supaul, Kahagaria, Katihar and Araria districts [61,62]. In the 2010 flood event, it was reported that Khagaria, Supaul, Araria, Katihar, and Madhepura districts were most adversely affected and the detailed flood maps based on ALOS and RADASAT satellite can be found in Amarnath et al [63] and FMISC Flood Report [34].…”
Section: Discussionmentioning
confidence: 99%
“…Blue dotted line represents the active floodplain in 1907. Many Satellite-derived products were produced to study this event [38][39][40]. The images show how the water occupies most of the early twentieth C. floodplain.…”
Section: Study Case: Dera Ghazi Khan and The River Indusmentioning
confidence: 99%
“…Strategies developed by human societies inhabiting Indus alluvial plains adapt the constructed social landscape to the geomorphological conditions and, at the same time, respond to the particular historical socio-political and cultural environment. Monitoring of the river conditions, the building of hydraulic infrastructure, and mobility summarises the basic elements of the management systems documented in the nineteenth century Indus valley [43], and they are not far from current approaches of 23 to flood management [31,34,36,40,56]. It is only to be expected that these were part of the landscape management strategies of past societies inhabiting this type of environment.…”
Section: Historical Social Responses To River Morphodynamicsmentioning
confidence: 99%
“…Moreover, the use of remote sensing techniques appears to be fundamental even for flood risk management (Franci et al 2014;Amarnath & Rajah 2015). Bryant and Gilvear (1999) used remote sensing to quantify geomorphic changes in the Tay River (Scotland), coupling the identification of land-use changes in riparian areas and the identification of bathymetric changes (derived from wavelength range -bandwidth and reflectance) for the riverbed.…”
Section: Introductionmentioning
confidence: 99%